2019
DOI: 10.1002/jobm.201900102
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of SE‐P3, P16, P37, and P47 bacteriophages infecting Salmonella Enteritidis

Abstract: The aim of this study was to identify and characterize the SE-P3, P16, P37, and P47 phages infecting Salmonella Enteritidis. Transmission electron microscopy analysis showed that the SE phages belonged to the Myoviridae or Siphoviridae family and had plaque sizes between 0.622 ± 0.027 and 1.630 ± 0.036 mm in diameter. sefC, pefA, spvC, sopE, and gipA virulent gene regions were absent in their genome and their calculated genome sizes were between 35.9 and 37.8 kbp. Sodium dodecyl sulfate polyacrylamide gel elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Li et al (2019) reported that the optimal MOI for E. coli phages (IME281, IME338, IME339, IME340, and IME341) was 0.001. A low MOI is an advantage in the large-scale application, phage production and can thus effectively reduce the overall cost of a commercial phage preparation (Wong et al, 2014;Bao et al, 2015;Yildirim et al, 2019).…”
Section: Application Of Bacteriophages In Artificially Contaminated Fmentioning
confidence: 99%
“…Li et al (2019) reported that the optimal MOI for E. coli phages (IME281, IME338, IME339, IME340, and IME341) was 0.001. A low MOI is an advantage in the large-scale application, phage production and can thus effectively reduce the overall cost of a commercial phage preparation (Wong et al, 2014;Bao et al, 2015;Yildirim et al, 2019).…”
Section: Application Of Bacteriophages In Artificially Contaminated Fmentioning
confidence: 99%
“…The phage was propagated according to the method of Yildirim et al (2019) with some modifications. The phage samples (100 μL) and active bacterial culture (300 μL) were transferred to 4 mL LB soft agar (LB broth +0.7% agar) at 45–50°C and vortexed (Reax top, Heidolph, Germany), and then poured onto empty Petri dishes.…”
Section: Methodsmentioning
confidence: 99%
“…The thermal stabilities of the free (Figure 3a) and encapsulated (Figure 3b The broad pH stability is an important property for evaluating the potential utilization of phages as bio-protective in acidic, neutral, and alkaline foods. Resistance to acidic conditions is also a significant feature in therapeutic applications (Yildirim et al, 2019). The pH stability of free and encapsulated phages was also evaluated in a broad pH range (1-13) for 1 h at 37 C (Figure 3c).…”
Section: Thermal and Ph Stability Of The Free And Encapsulated Phagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Modern proteomics needs immense powers of resolution, sensitivity, and speed of identifi cation, which so far can be reached through One and/or Two Dimension (1D, 2D) gels in combination with advanced analysis of complex protein distributions in automated fashions considering the large number of diff erent protein interaction domains to provide important data sets [4,5]. Usually, the common technique used to investigate cell protein profi les is Sodium Dodecyl Sulphate-Polyacrylamide Gel Electrophoresis (SDS-PAGE), which contains separating proteins by isoelectric charge or molecular weight [6][7][8][9]. For a deep understanding of the relevant bacteriophages' proteins biology, this information must be integrated with analytical data from various ' bioinformatics levels' including DNA sequence, mRNA profi les, protein expression and metabolite concentrations as well as information about dynamic spatio-temporal changes in these molecules [10].…”
Section: The Assembly Of Bacteriophage Functional Enzymatic Models Inmentioning
confidence: 99%